Good Governance pada dunia Perguruan Tinggi - Agung Waluyo (Jurnal Akuntansi Bisnis, 2017)
In this time, Good Governance is mandatory,  just not in business corporation, but also needed in government sector, Non Government Organisation, etc. The ecencial of Good Governance   is acuntability, transparancy and implementation of ethic in his duty and their function, such as corporate ethic, social ethic and  nation state ethic.Good Governance in University is first step proactive action to  protect  from internal conflict.  Good Governance Implementation is a final implementation from Risk Management, Control management and acuntability principle.  Keyword : Good Governance,  Perguruan Tinggi, Risk Management, Control Management